2003
DOI: 10.1081/jas-120018780
|View full text |Cite
|
Sign up to set email alerts
|

Formoterol Delivered via the Dry Powder Aerolizer® Inhaler Versus Albuterol MDI and Placebo in Mild-to-Moderate Asthma: A Randomized, Double-Blind, Double-Dummy Trial

Abstract: The objectives of this study were to compare the efficacy and tolerability of twice-daily formoterol dry powder 12 microg and 24 microg (Foradil) delivered via Aerolizer inhaler with four times daily albuterol (salbutamol) 180 microg delivered via metered dose inhaler (MDI) and placebo. A total of 554 adolescents and adults (ages 12-75 years) with mild-to-moderate asthma were randomized to this 12-week, multicenter, double-blind, double-dummy, placebo-controlled, parallel-group study. Twelve-hour spirometry me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…(8) Foradil Aerolizer delivers single 12-g doses of formoterol, and has been shown to provide effective long-term disease control in a range of patients with varying degrees of severity of asthma and COPD. (9)(10)(11)(12)(13) The Aerolizer has also been used more recently in some countries for delivery of budesonide (Miflonide Aerolizer, Novartis Pharma AG, Basel, Switzerland) and beclomethasone (Miflasone Aerolizer, Pharma AG, Basel, Switzerland). (14) The aim of the current study was to compare in vitro the particle size distribution, emitted dose and device resistance of formoterol delivered via Foradil Aerolizer device with formoterol delivered via a non-proprietary single-dose capsule inhaler.…”
Section: Introductionmentioning
confidence: 99%
“…(8) Foradil Aerolizer delivers single 12-g doses of formoterol, and has been shown to provide effective long-term disease control in a range of patients with varying degrees of severity of asthma and COPD. (9)(10)(11)(12)(13) The Aerolizer has also been used more recently in some countries for delivery of budesonide (Miflonide Aerolizer, Novartis Pharma AG, Basel, Switzerland) and beclomethasone (Miflasone Aerolizer, Pharma AG, Basel, Switzerland). (14) The aim of the current study was to compare in vitro the particle size distribution, emitted dose and device resistance of formoterol delivered via Foradil Aerolizer device with formoterol delivered via a non-proprietary single-dose capsule inhaler.…”
Section: Introductionmentioning
confidence: 99%
“…There were six deaths identified in the AstraZeneca database which were not reported in the published manuscripts [28][29][30][31]. The cause of death in the study of PLESKOW et al [32] was stated to be cardio-respiratory; however, in the Novartis FDA submission, this was revised to ''asthma-related death''. In the report by VON BERG et al [33], the death was initially attributed to a subarachnoid haemorrhage; however, the AstraZeneca database reported the cause of death as respiratory failure/asthma related, as subsequently reported in an erratum [34].…”
Section: Documentation Of Deathsmentioning
confidence: 86%
“…There were nine deaths due to asthma (table 1), and 33 deaths due to other causes, of which 18 were attributed to cardiac causes (table 2) [26,[28][29][30][31][32][33][34][35][36][37][38][39]. Among the patients who died from asthma, five out of the seven patients randomised to formoterol were prescribed ICS (either as randomised or background maintenance therapy), and one out of two patients randomised to non-LABA comparator treatment was prescribed ICS (either as randomised or background maintenance therapy).…”
Section: Main Findingsmentioning
confidence: 99%
“…No comparable data are available for other ICS/LABA combinations such as fluticasone propionate/salmeterol or beclometasone/ formoterol. In the present study the top and bottom daily dose levels of the fluticasone/formoterol dose range were evaluated, since multiple previous studies have shown minimal pairwise differences in effect between contiguous dose levels of ICS and β2-agonist monotherapies in asthma [10][11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%